2012
DOI: 10.1002/bdd.1809
|View full text |Cite
|
Sign up to set email alerts
|

Active intestinal absorption of fluoroquinolone antibacterial agent ciprofloxacin by organic anion transporting polypeptide, Oatp1a5

Abstract: Fluoroquinolone antimicrobial drugs are absorbed efficiently after oral administration despite of their hydrophilic nature, implying an involvement of carrier-mediated transport in their membrane transport process. It has been that several fluoroquinolones are substrates of organic anion transporter polypeptides OATP1A2 expressed in human intestine derived Caco-2 cells. In the present study, to clarify the involvement of OATP in intestinal absorption of ciprofloxacin, the contribution of Oatp1a5, which is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…These transporters are sometimes major determinants of the dispositional fate of drugs, including antibiotics commonly used in the treatment of infections (8,9). For example, in the process of absorption into the body, fluoroquinolones and ␤-lactams are predominantly absorbed via organic anion-transporting polypeptides (OATPs) and peptide transporter 1 on the intestinal membrane barrier (8)(9)(10). In contrast, there are several reports that fluoroquinolones absorbed into enterocytes are expelled by the ATP-binding cassette (ABC) drug efflux transporter P-glycoprotein (P-gp; MDR1/ABCB1) and breast cancer resistance protein (BCRP/ABCG2) back into the gut lumen (11).…”
mentioning
confidence: 99%
“…These transporters are sometimes major determinants of the dispositional fate of drugs, including antibiotics commonly used in the treatment of infections (8,9). For example, in the process of absorption into the body, fluoroquinolones and ␤-lactams are predominantly absorbed via organic anion-transporting polypeptides (OATPs) and peptide transporter 1 on the intestinal membrane barrier (8)(9)(10). In contrast, there are several reports that fluoroquinolones absorbed into enterocytes are expelled by the ATP-binding cassette (ABC) drug efflux transporter P-glycoprotein (P-gp; MDR1/ABCB1) and breast cancer resistance protein (BCRP/ABCG2) back into the gut lumen (11).…”
mentioning
confidence: 99%
“…Early pharmacokinetic research has shown that some fluoroquinolones are absorbed efficiently from the small intestine and transported by organic anion transporting polypeptides (OATPs) [50]. Colin et al [51] investigated adequate moxifloxacine concentrations using a population pharmacokinetic analysis and pharmacokinetic-pharmacodynamic simulations in post-bariatric surgery patients.…”
Section: Bioavailability Of Drugs After Bypassmentioning
confidence: 99%
“…Fluoroquinolones were widely used in human and veterinary medicine for the treatment of infectious diseases [5][6][7]. Ciprofloxacin, a fluoroquinolone antibacterial agent [8,9], has a wide range of antibacterial activity, which is highly active against various Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%